Espaços Fuzzy e aspectos quânticos dos buracos negros - Silva, Carlos Alex Souza da (2011)
A model based on the topology change of a quantum manifold is used to explain the origin of the black hole thermodynamics. Some important issues are addressed, for example, why black holes obey a generalized second law of thermodynamics. The method we use to do this is to analyze the selection rules for black hole area transitions in the evaporation process driven by topology change. A discrete spectrum, which becomes increasingly spaced as the black hole approaches the Planck scale, is obtained for the black hole area. The black hole information loss paradox is also addressed.